Contemporary Identity. The Historical and Contemporary Criteria of Evaluation - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to discuss the meaning of the notion of national identity in contemporary society. The argument is developed by discussing the relation between the social and the individual aspects of identity. First, the author analyzes the connection between the individual and the social aspects of identity in the modern conception of nation. He argues that the idea of an ethnic community served as a centre to relate the individuals before and beyond the nation. Second, the argument is developed by claiming that in the times of intensified communication the relation with the centre undergoes important change. The author argues that the diminishing distance between the centre and the periphery results in a problematization of the national identity: identity is thought of as either over-determined or under-defined by the social actors. Third, because of such changes national identity becomes defined not in terms of centre and periphery but in terms of individual possibilities of choise.